INTEGRASI ISU KONTEMPORER DALAM PEMBELAJARAN ILMU PENGETAHUAN ALAM DAN SOSIAL PADA KURIKULUM MERDEKA DI SEKOLAH DASAR - Yona Dwi Kusumawati; Adhistya Putri; Dynar Ayu Puspita Rukmi; Muhammad Imaduddin; Arif Mahya Fanny (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Theory and textbook-oriented learning often results in meaningless learning experiences and fails to develop students’ critical thinking skills with regard to social issues. Contextual learning is expected to help students understand the purpose of learning and relate it to everyday life. This study aims to analyze the implementation of contemporary issues in IPAS teaching within the Merdeka Curriculum at primary school. The research takes a qualitative approach, emphasizing an in-depth understanding of teachers’ experiences, opinions, and practices in classroom learning activities. The findings reveal that teachers have integrated contemporary issues into teaching module development, the learning process, media, and contextual problem-based discussion activities relevant to students’ daily lives, Contemporary issues were integrated through PBL, utilizing video and online news, as well as discussion and direct observation activities in the community. This approach made students more active and enthusiastic learners who were better able to understand the material because it was relevant to their real-life experiences. Furthermore, integrating contemporary issues was proven to enhance students critical thinking, collaboration, communication, and social awareness.